Higgs discovery : the power of empty space - Randall, Lisa. (New York: HarperCollins, 2011)
Randall, the Frank J. Baird, Jr., Professor of Science at Harvard University and the author of New York Times Notable Books Knocking on Heaven's Door and Warped Passages, explains the science behind the monumental Higgs boson discovery, its exhilarating implications, and the power of empty space.--
"On July 4, 2012, physicists at the Large Hadron Collider in Geneva made history when they discovered an entirely new type of subatomic particle that many scientists believe is the Higgs boson. For forty years, physicists searched for this capstone to the Standard Model of particle physics--the theory that describes both the most elementary components that are known in matter and the forces through which they interact. This particle points to the Higgs field, which provides the key to understanding why elementary particles have mass."--
Higgs discovery : the power of empty space -- An excerpt from Warped passages. Chapter 10: The origin of elementary particle masses : spontaneous symmetry breaking and the Higgs mechanism -- An excerpt from Knocking on heaven's door. Chapter 16: The Higgs boson.
Keywords: Higgs bosons; Higgs bosons